Hadith #2771 - Sahih Muslim - Nubaih bin Wahb (Sahih Muslim)
We went with Aban b. Uthman (in a state of lhram). When we were at Malal the eyes of Umar b. Ubaidullah became sore and, when we reached Rauba’ the pain grew intense. He (Nubaib b. Wahb) sent (one) to Aban b. Uthman to ask him (what to do). He sent him (the message) to apply aloes to them, for ‘Uthman (Allah be pleased with him) reported that the Messenger of Allah (ﷺ) applied aloes to the person whose eyes were sore and he was in the state of Ihram.
Grade: Sahih

Hadith #3324 - Sahih Muslim - Nubaih bin Wahb (Sahih Muslim)
I heard ‘Uthman b. ‘Affan say that Allah’s Messenger (ﷺ) had stated: A Muhrim must neither marry himself, nor arrange the marriage of another one, nor should he make the proposal of marriage.
Grade: Sahih

Hadith #3325 - Sahih Muslim - Nubaih bin Wahb (Sahih Muslim)
Umar b. Ubaidullah b. Ma’mar sent me to Aban b. Uthman as he wanted to make the proposal of the marriage of his son with the daughter of Shaiba b. Uthman. He (Aban b. Uthman) was at that time (busy) in the season of Pilgrimage. He said: I deem him to be a man of the desert (for it is a common thing) that a Muhrim can neither marry, nor is he allowed to be married to anyone. It is Uthman (b. Affan) who reported this to us from Allah’s Messenger (ﷺ).
Grade: Sahih

Hadith #3328 - Sahih Muslim - Nubaih bin Wahb (Sahih Muslim)
I intend to marry Talha b. ‘Umar and I earnestly desire you to be present there (in this ceremony of marriage). Aban said to him: I find you a block-headed ‘Iraqi. I heard ‘Uthman b. ‘Affan say that Allah’s Messenger (ﷺ) said: A Muhrim should not marry.
Grade: Sahih